Nurses' Expectations of an Inpatient Portal for Hospitalized Patients and Caregivers - Hoonakker, Peter L. T.; Rankin, Rebecca J.; Passini, Jennifer C.; Bunton, Jenny A.; Ehlenfeldt, Bradley D.; Dean, Shannon M.; Thurber, Anne S.; Kelly, Michelle M. (Applied Clinical Informatics, 2019)
Background Patient portals are intended to engage patients and enhance patient-centered care. Recent studies suggest that the information within portals could provide benefits to patients and their caregivers during hospitalization; however, few studies have examined nurse and staff expectations of portals when used in the hospital setting.Objective This article examines inpatient nurse and support staff expectations of a commercially available inpatient portal prior to its hospital-wide implementation.Methods In this cross-sectional study, nurses and support staff were surveyed 1 month prior to the implementation of an inpatient portal for patients. Items included respondent characteristics, satisfaction with online inpatient portal training, expectations of the effects of portal use on patients, caregivers, and staff, overall acceptance, and barriers to its implementation.Results Of 881 respondents, 73.0% were staff nurses, 18.4% nurse assistants, 4.3% unit coordinators, and 1.2% nurse managers. Respondents were generally satisfied with the portal information they received from online training. A majority liked the portal to some extent prior to its use (66.7%); however, they noted multiple implementation barriers, including: tablets would get lost/damaged (66.2% of respondents), patients and/or caregivers would have too many questions (48.5%), and staff would have problems integrating it into their workflow (44.7%). Respondents working on medical units had higher expectations (p < 0.001) and acceptance (p < 0.01) of the portal than those on surgical and intensive care units. Nurse managers were more positive than respondents with other job roles were (all p < 0.001).Conclusion Overall, nurse and support staff had high expectations of the effects of inpatient portal use prior to its hospital-wide implementation. They thought it would benefit patients and/or their caregivers; however, they also perceived several barriers to its implementation. These results will be used in conjunction with patient and caregiver perspectives to inform future efforts to evaluate and improve upon inpatient portal implementation and dissemination across health systems.
Keywords: patient portal; inpatient; implementation; expectations; nurses and staff personnel